2021
DOI: 10.3389/fvets.2021.645561
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination With Recombinant Adenoviruses Expressing the Bluetongue Virus Subunits VP7 and VP2 Provides Protection Against Heterologous Virus Challenge

Abstract: Bluetongue virus (BTV) is the causative agent of a disease that affects domestic and wild ruminants and leads to critical economic losses. BTV is an arbovirus from the Reoviridae family that is typically transmitted by the bite of infected Culicoides midges. BTV possesses multiple serotypes (up to 28 have been described), and immunity to one serotype offers little cross-protection to other serotypes. The design of vaccines that provide protection across multiple serotypes is therefore highly desirable to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Jeggo et al also showed that T cell adoptive transfer from BTV-recovered sheep protected from BTV challenge in monozygotic twins [ 41 ]. Cellular immunity in absence of neutralizing antibodies typically only provides partial protection [ 41 , 43 ], but it is cross-reactive between serotypes [ 44 , 45 , 46 , 47 , 48 , 49 ]. Indeed, vaccination based on BTV antigenic determinants that are conserved between serotypes (such as VP7 or NS1) have shown promising results in eliciting at least partial cross-serotype protection in animal models [ 44 , 46 ].…”
Section: The Control Of Btv By Host Immunitymentioning
confidence: 99%
“…Jeggo et al also showed that T cell adoptive transfer from BTV-recovered sheep protected from BTV challenge in monozygotic twins [ 41 ]. Cellular immunity in absence of neutralizing antibodies typically only provides partial protection [ 41 , 43 ], but it is cross-reactive between serotypes [ 44 , 45 , 46 , 47 , 48 , 49 ]. Indeed, vaccination based on BTV antigenic determinants that are conserved between serotypes (such as VP7 or NS1) have shown promising results in eliciting at least partial cross-serotype protection in animal models [ 44 , 46 ].…”
Section: The Control Of Btv By Host Immunitymentioning
confidence: 99%
“…However, they also indicate that it is important to consider the possibility of ADE responses when designing vaccination campaigns using serotypespecific inactivated or subunit vaccines. To prevent problems that could be caused by ADE, vaccines should include components that induce a more widely cross-serotype protective immune response, for example the more highly conserved BTV non-structural proteins NS1 and NS2, or structural protein VP7, which induce cross-reactive and protective T-cell mediated responses [2,55].…”
Section: Discussionmentioning
confidence: 99%
“…Several platforms have been employed to induce immunity to BTV in the natural host. These include, among others, poxviruses [128][129][130], adenoviruses [130][131][132], Rift Valley fever virus (RVFV) [133,134], or herpesviruses [135,136]. These recombinant constructs were able to induce immunity to BTV in murine models and/or in the natural host, and protection was also demonstrated in some studies in the natural host [129][130][131]133,134].…”
Section: Btv Vaccines: Live Attenuated Inactivated or Recombinant Vaccines?mentioning
confidence: 99%
“…They are non-pathogenic as they are often based on replication-defective viruses. They can offer protection over multiple BTV serotypes with the same formulation [128,132]. Recombinant vector vaccines based on attenuated vaccine strains, such as RVFV, can even induce bivalent protection in ruminants against RVFV and BTV [133].…”
Section: Btv Vaccines: Live Attenuated Inactivated or Recombinant Vaccines?mentioning
confidence: 99%